The reasoning as an element of nursing care for people living with HIV/aids (Research, Society and Development, 2020)
Objective: Reflect on the reasoning and its implications on nursing care to people living with HIV/AIDS. Method: This is a theoretical-reflexive study, theoretical issues were discussed and how they fit into the health field, having reasoning as a tool of care to people living with HIV/AIDS, because in order to have proper reasoning, it is essential to present information in a comprehensive way to all, because the basis of reasoning is knowledge and understanding. Results and discussion: We understood that in order to understand the ways of care to this population, it is necessary to understand beyond the biological and pathological aspects, the social, cultural, psychological, economic and political aspects, i. e., any kind of situation that implies in susceptibility to disease. Final considerations: We propose the use of reasoning as an indispensable element for nursing care, this must come at an opportune time for the exchange of knowledge and strengthening of ties so that it promotes care.